The Popular Anthropocene in Global Climate (Dis)Governance - Paola Huwe de Paoli (Journal of World-Systems Research)
The climate emergency is posing an existential threat to millions of species on Earth—including humans. Despite advances in climate science and the consolidation of global climate governance—which establishes processes, rules, and agreements that define mitigation strategies—the climate emergency has accelerated in the late twentieth and early twenty-first centuries. At the same time, the popular anthropocentric conception, which presents a standard narrative about the genesis and conditioning factors of the climate emergency, prevails in the dialogues, negotiations, and strategies of global climate governance. Therefore, this article analyzes whether the propositions of global climate governance inspired by the popular Anthropocene are sufficient to define mitigation strategies in the face of approaching tipping points. The intellectual-ideological axioms of the popular Anthropocene, namely the carbon metric, sustainable development, and the green economy, are chosen as research criteria. It should be reiterated that popular anthropocentric propositions are not sufficient to delimit effective mitigation strategies; this is because they contemplate modern rationality and reformist liberalism, and therefore aim for “sustainable capitalism”—an oxymoron, since a balanced metabolic relationship with nature is opposed to the incessant accumulation of capital, the driving force of historical capitalism.